Low-cost Internet of Things (IoT)-enabled a wireless wearable device for detecting potassium ions at the point of care - Ozer, Tugba; Agir, Ismail; Henry, S. Charles (ELSEVIER SCIENCE SA, 2022)
We present a wearable device for wireless monitoring of potassium in sweat. The device consists of an all-solidstate ion-selective electrode (ISE) and a miniaturized printed circuit board (PCB) for potentiometric readout and processing. Stencil-printed carbon electrodes (SPCE) were fabricated on PET substrates using various types of graphite for comparison of sensor performance and were modified with carbon black to enhance sensor performance. The PCB readout module includes a low-power Wi-Fi interface for transmitting data real-time to a smartphone application, which can calculate potassium concentrations using a software algorithm and display the results on an OLED screen. The potassium selective ISE showed a response (< 11 s) to K+ with good sensitivity (56.1 +/- 0.7 mV decade-1) and a linear range of 10-4-10-1 M with an LOD of 1 x 10-5 M. As a proof-ofconcept, we demonstrate the applicability of the SPCE-ISE coupled to the wireless potentiometer operated from a smartphone for point-of-care testing (POC) of potassium in artificial sweat. The wearable Internet of Things (IoT) device uses an Arduino supported, Wi-Fi embedded microcontroller to transfer data. We reduced the cost of analysis compared to commercially available read-out devices using our potentiometer (< $25). This work represents a significant step forward as it is one of the first systems that integrates both sensing and data display in real-time on a device compatible with wearable applications by untrained users, making POC testing easier to fit into daily life.
Keywords: Ion-selective electrode; Potassium; Potentiometric detection; Point -of -care test; Wireless wearable device; Internet of things; SELECTIVE ELECTRODES; CARBON-BLACK; POTENTIOMETRIC SENSORS; CONDUCTING POLYMER; PERFORMANCE; SODIUM; COEFFICIENTS; LAYERS; Chemistry; Electrochemistry; Instruments & Instrumentation